PENAMBAHAN TREHALOSE DALAM PENGENCER TRIS KUNING TELUR TERHADAP KUALITAS SEMEN SAPI PESISIR - Auli Two Putra Syahminan; Jaswandi Jaswandi; Tinda Afriani (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2023)
The purpose of this study was to find out how the semen quality of pesisir cattle was after the addition of trehalose to egg yolk tris diluent. The research material in the form of fresh semen was obtained from pesisir cattle aged approximately 4 years and the quality of the semen had been tested by observing the quality of fresh semen before dilution.. This study used a randomized block design with 4 treatments and 4 replications. The treatment given was the addition of trehalose in egg yolk tris diluent. The treatment given consisted of control, the addition of trehalose 0.5%, 1%, and 1.5%. The variables in this study included motility, viability, intact plasma membrane (MPU), and intact acrosome cap (TAU) of spermatozoa of pesisir cattle. The results of this study indicated that the addition of trehalose had a significant effect (p<0.05) on the viability, MPU, TAU, and did not show a significant effect (p>0.05) on the motility of spermatozoa of pesisir cattle. The results of this study indicated that the dose of trehalose addition of 1.5% in egg yolk tris diluent showed the best results on the quality of spermatozoa of pesisir cattle, where motility was found to be 53%, viability 61%, MPU 63%, and TAU 63%. Keywords : Trehalose, Pesisir Cattle, Semen Quality of Pesisir Cattle.